The Dynamic of Insect Population Succession in Bird Poisoned by Pyrethroid Insecticides - Muhammad Falikhul Musyaffa'; Susi Soviana; Elok Budi Retnani (Acta VETERINARIA Indonesiana, 2021)
Insecticide poisoning is one of the causes of death in wild birds. One of the insecticides that are often used is a pyrethroid. This study aims to determine the succession of insects in birds intoxicated by pyrethroid pesticide. This research was conducted in Dramaga campus, IPB University, Bogor, Indonesia. One quail (Coturnix coturnix japonica) was used as a control which was killed by manual neck dislocation, and one bird was treated orally treated with acute dose pyrethroid pesticide. Cadavers are placed in insect traps until they reach the skeletal stage of decomposition. Insects that enter the trap are collected every 6 hours for 24 hours, from the first day until the whole process of decomposition of the carrion reaches the skeletal stage. Then the insects are identified and counted. The results showed that the cadaver decomposition process in the treatment group took longer than the control group. In the control group, insects arrived for approximately 138 hours after the cadaver was placed, while the treatment group took approximately 324 hours. The types of insects in these two groups are relatively the same, namely flies (Order Diptera: Calliphoridae, Muscidae), cockroaches (Order Dictyoptera: Blattidae and Blaberidae) and Sarcophagidae), beetles (Order Coleoptera: Scarabidae), ants (Order Hymenoptera: Formicidae), earwigs (Order Dermaptera: Anisolabididae). Chrysomya megachepala was the dominant insect over the others and was always present from the early stages to post-decay in control and pyrethroid treatment.